RELATIONSHIP OF MARKETING ASPECTS, FINANCIAL, FUNDS, TECHNICAL, MANAGEMET ON CUT CREDITS IN BANK MANDIRI ANEKA TAMBANG IN JAKARTA - Reza Suriansha; Erwin Rasyid; Alfonsus Beo Say (Sebatik, 2020)
PT. Bank Mandiri is the largest bank in Indonesia in terms of assets, loans, and deposits. But at this time Bank Mandiri is experiencing a large number of customers that are doing bad credit. The research was conducted related to the number of bad loans experienced by PT. Bank Mandiri, Jakarta. The purpose of this study is to determine the relationship of internal factors, which include aspects of marketing, aspects of financial arrangements, aspects of funds, technical aspects, and management aspects partially and simultaneously on the customer's bad credit. The method used is quantitative by using correlation analysis techniques. The method of data collection is carrying out by collecting and submitting research questionnaires to debtors using the Bank Mandiri (PERSERO) TBK branch of the Jakarta Building Aneka Tambang branch that experiences cut credit, and studies documents relating to cut credit. This event obtaining from books and literature, related research journals. The analysis tool used is multiple regression analysis using SPSS software version 22. Partially, using the t-test of the marketing aspects, financial management aspects, funding aspects, technical aspects, and management aspects of bad credit. From the research results obtained aspects of financial management, technical aspects and management aspects have a positive and significant correlation to the increase in cut credits of PT. Mandiri Bank. Then, the marketing and funding variables correlate negatively and significantly to bad loans so that the increasing aspects of marketing and funding aspects, the cut credit decreases. From the simultaneous test results of the independent variables on the dependent variable, it knowing that the marketing aspects, financial management aspects, funding aspects, technical aspects, and management aspects have a significant and significant influence on the cut credits of Bank Mandiri in the Aneka Tambang Jakarta branch in Jakarta.